Total Synthesis of Atisane-Type Diterpenoids and Related Diterpenoid Alkaloids - Zhu, Guili; Liu, Rong; Liu, Bo (Synthesis, 2015)
Atisane-type compounds and related natural products are attractive for their molecular skeletons and pharmaceutical bioactivities. This review summarizes total syntheses of atisane-type diterpenoids and related diterpenoid alkaloids.1 Introduction2 Total Synthesis and Synthetic Studies of Atisane-Type Diterpenoids and Related Diterpenoid Alkaloids2.1 Ionic Methods2.1.1 SN2 Substitution Reaction2.1.2 Aldol Reaction2.1.3 Intramolecular Double Michael Addition2.2 Free-Radical Methods2.2.1 Free-Radical Rearrangement2.2.2 Free-Radical Addition2.3 Diels–Alder Cycloaddition3 Conclusion
Keywords: atisane; diterpenoids; alkaloids; total synthesis; bicyclo[2.2.2]octane